2020
DOI: 10.1261/rna.074864.120
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of highly structured RNA with multicomponent deoxyribozyme probes at ambient temperatures

Abstract: Molecular analysis of RNA through hybridization with sequence-specific probes is challenging due to the intrinsic ability of RNA molecules to form stable secondary and tertiary structures. To overcome the energy barrier toward the probe-RNA complex formation, the probes are made of artificial nucleotides, which are more expensive than their natural counterparts and may still be inefficient. Here, we propose the use of a multicomponent probe based on an RNA-cleaving deoxyribozyme for the analysis of highly stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…This perfect selectivity is not surprising considering significant difference in the genomes of the alternative viruses and the ability of BiDz to differentiate single nucleotide substitutions in broad temperature ranges. [15] We then investigated the ability of 4DNM to accurately recognize the presence of CoV2 in human clinical samples. RNA samples were isolated from 14 patients according to the standard procedure for RNA preparation for RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This perfect selectivity is not surprising considering significant difference in the genomes of the alternative viruses and the ability of BiDz to differentiate single nucleotide substitutions in broad temperature ranges. [15] We then investigated the ability of 4DNM to accurately recognize the presence of CoV2 in human clinical samples. RNA samples were isolated from 14 patients according to the standard procedure for RNA preparation for RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Another advantage is its high selectivity towards single nucleotide substitutions (SNS). [12,15] This is achieved by shortening Arm 2 complementary to the SNS site (Figure 1A). Short arm binds only the fully complementary, but not single base mismatched sequences.…”
Section: Introductionmentioning
confidence: 99%
“…These LOD values, while unable to compete with the LODs of PCR-based assays ( Braun et al, 2021 ), are in the same range as the LOD reported for the molecular beacon probe (MBP) ( Kolpashchikov 2012 ). Unlike MBP, which cannot efficiently interrogate a structured nucleic acid target ( Nguyen et al, 2011 ; Reed et al, 2020 ), the split junction probe used in the aptamer-expressing assay can tolerate stable secondary/tertiary structures a natural RNA target generally acquires. Here, this advantageous property of the split probes was used to target native 16S rRNA sequences of bacterial species.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the affinity of the 3WJ probe to the target was maintained by the length of the TP strand. Previously, we have shown that even if one component of the split probe is shortened to allow for discrimination of point mutations, the length of the target-recognizing fragment of another probe’s component controls the overall affinity to keep the signal high ( Gerasimova et al, 2015 ; Reed et al, 2020 ). This illustrates the advantage of split hybridization probes over monolith ones—the ability to cope with the affinity-specificity dilemma that may compromise performance of monolith probes ( Demidov and Frank-Kamenetskii, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation